2017
DOI: 10.1111/scs.12501
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning the future as expressed within family health conversations by families of persons suffering from stroke

Abstract: The persons with stroke and their belonging family members' vision of the future was reflected over in the light of theories about beliefs, possible selves, hope and suffering, and the findings highlight the need for broader use of family conversations to support persons with stroke and their families to manage the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…We also found that the FSNCs had helped the family members move on by enabling them to identify and develop solutions to their problems. This finding aligns with past results showing that listening to each other in the family increased mutual understanding and resulted in empowering and affirming behaviour [ 18 , 40 , 42 ]. Several other studies have underscored the strong healing effect of FSNCs [ 19 , 43 , 44 ], both on participants as individuals and at family level [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that the FSNCs had helped the family members move on by enabling them to identify and develop solutions to their problems. This finding aligns with past results showing that listening to each other in the family increased mutual understanding and resulted in empowering and affirming behaviour [ 18 , 40 , 42 ]. Several other studies have underscored the strong healing effect of FSNCs [ 19 , 43 , 44 ], both on participants as individuals and at family level [ 40 ].…”
Section: Discussionsupporting
confidence: 92%